PET/CT Has Greater Diagnostic Utility in Patients with Sinonasal Malignancy. (23rd August 2013) - Nishtala, Arvind; Mercier, Gustavo; Grillone, Gregory A.; Jalisi, Scharukh; Truong, Minh‐Tam; Subramaniam, Rathan; Devaiah, Anand K.
Abstract : Objectives: In sinonasal malignancy, the use of fused positron emission tomography/computed tomography (PET/CT) may help clinicians in decision making more than standard CT +/‐ magnetic resonance imaging (MRI). Methods: A retrospective review of sinonasal malignancy patients undergoing PET/CT imaging between 2005 and 2011 at our institution was performed. Eighteen patients met all inclusion criteria: PET/CT performed with treatment and follow‐up at our institution. Histology, staging, imaging data, imaging reports, treatments, follow‐up, and disease status were compiled. A 6‐variable scoring system (tumor involvement, regional disease detection, distant metastases detection, malignant determination, tumor avidity, change in treatment) to examine imaging utility was devised. Results: In 12 patients (67%), PET/CT was superior to CT/MRI, while the latter was superior in only 3 patients (16%). Neither modality was superior in 3 patients (16%). PET/CT was able to identify regional or distant disease in 8 patients (44%), while CT/MRI did not (0%). CT/MRI showed more potentially involved tissue than in PET/CT. In 8/18 patients (44%), PET/CT could better distinguish between malignant and non‐malignant tissue; 10/18 patients (56%) were equivocal. The use of PET/CT led to a documented change in the patient's treatment plan in 11/18 patients (61%), compared to 1/18 change for CT/MRI (5%). In looking at overall utility of PET/CT vs CT/MRI in the 6 variables, PET/CT scored significantly higher (Chi‐squared, P = 0.02). Conclusions: For sinonasal malignancies, PET/CT better identifies regional and distant involvement, and malignant from non‐malignant tissue. Compared to CT/MRI data, PET/CT has a greater impact on the treatment and management of patients.